Pneumomediastinum following immunization of BioNTech COVID-19 vaccine: A coincidence? - Shen-Hao Lai; Sui-Ling Liao (Pediatric Respirology and Critical Care Medicine)
Background: To build immunity against the pandemic severe acute respiratory syndrome coronavirus-2 infection in adolescents, wide-ranging immunization with BioNTech (BNT) vaccine was initiated in September 2021 in Taiwan. Some adverse events are, therefore, reported after vaccination. Herein, we stated a case series with uncommon pneumomediastinum after BNT vaccination.Materials and Methods: This study retrospectively enrolled adolescents, who being diagnosed to have pneumomediastinum, during the 3-month period (between September 22, 2021, and December 22, 2021). Clinical information, such as clinical symptoms, radiographic characteristics, and clinical outcomes, were further analyzed.Results: A total of eight adolescents developed pneumomediastinum during the 3-month period after BNT vaccination. The time interval between pneumomediastinum and vaccination showed bimodal peak (around 10 and 60 days after BNT vaccination). Significant Macklin effect can be sketched in radiographic images of six patients.Conclusion: Several cases of pneumomediastinum were found in adolescents after BNT vaccination. The precise association is needed for further investigation.